Predicting lying, sitting, walking and running using Apple Watch and Fitbit data - Fuller, D.; Rahimipour Anaraki, J.; Simango, B.; Rayner, M.; Dorani, F.; Bozorgi, A.; Luan, H.; Basset, F. A. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives This study`s objective was to examine whether commercial wearable devices could accurately predict lying, sitting and varying intensities of walking and running.